Impact of social distancing in the routine of children and teenagers with Autism Spectrum Disorder (Research, Society and Development, 2021)
In times of COVID-19, social distance is essential to prevent the virus' spread and to keep the population protected, however, this causes major changes in routines of individuals in general.  Among these are children and adolescents with Autistic Spectrum Disorder (ASD), who may be subject to greater impacts due to their resistance to changes due to restricted patterns of behavior. To analyze the impacts of social distance on the daily routine of children and adolescents with ASD. Cross-sectional research with a quantitative approach, carried out through the Google Form, which was composed of 37 questions, with the legal guardians of children and adolescents with ASD. The largest audience were children in early childhood with a mild degree in the disorder's classification; there was an increase in behavioral problems, emergence of compulsion or rejection of food; most children miss school and are doing alternative activities; there was also an increase in the difficulty in accepting activities outside the school environment; those responsible for the children had a greater participation in leisure.  The negative repercussion caused by the social detachment concomitant with the discontinuity of specialized treatment of children and adolescents with ASD was found; that triggered or intensified the disruptive behaviors.